2021
DOI: 10.4103/aja.aja_58_20
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract as a cryoprotectant additive to preserve the motility and DNA integrity of human spermatozoa

Abstract: Cryopreservation impairs sperm quality and functions, including motility and DNA integrity. Antioxidant additives in sperm freezing media have previously brought improvements in postthawed sperm quality. Green tea extract (GTE) is widely considered as an excellent antioxidant, and its beneficial role has been proven in other human cells. This study aims to evaluate the GTE as a potential additive in cryopreservation media of human spermatozoa. In part one, the semen of 20 normozoospermic men was used to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The positive benefit of antioxidant therapy observed in this study is in keeping with the important role that ROS-induced lipid peroxidation plays in the loss of sperm function and DNA integrity associated with cryopreservation (Figures 4-6). The finding of improved DNA integrity, in particular, is in keeping with the results obtained by others with a variety of antioxidants, including ebselen [54], resveratrol [55], vitamin C [55], canthaxanthin [56], curcumin [57], L-carnitine [58], green tea extract [59], catalase [60], Tempol [61], alpha lipoic acid [62], and vitamin E [63]. Such results reinforce the conclusion that DNA damage in cryostored spermatozoa is primarily induced by oxidative stress, rather than by alternative mechanisms such as apoptosis [37].…”
Section: Discussionsupporting
confidence: 88%
“…The positive benefit of antioxidant therapy observed in this study is in keeping with the important role that ROS-induced lipid peroxidation plays in the loss of sperm function and DNA integrity associated with cryopreservation (Figures 4-6). The finding of improved DNA integrity, in particular, is in keeping with the results obtained by others with a variety of antioxidants, including ebselen [54], resveratrol [55], vitamin C [55], canthaxanthin [56], curcumin [57], L-carnitine [58], green tea extract [59], catalase [60], Tempol [61], alpha lipoic acid [62], and vitamin E [63]. Such results reinforce the conclusion that DNA damage in cryostored spermatozoa is primarily induced by oxidative stress, rather than by alternative mechanisms such as apoptosis [37].…”
Section: Discussionsupporting
confidence: 88%
“…Some observational studies have revealed that increased frequency and duration of green tea consumption signi cantly improved sperm concentration and motility [30][31][32]. However, only one study has examined the effects of green tea consumption on human sperm DNA integrity [33]. To investigate whether green tea extract (GTE) exerted protective bene ts on human sperm DNA, Alqawasmeh et al divided the sperm of the subjects into three groups (control, 300 µmol/l H 2 O 2 , and 300 µmol/l H 2 O 2 + 1.0 ng/ml GTE) and measured the DFI for each group.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether green tea extract (GTE) exerted protective bene ts on human sperm DNA, Alqawasmeh et al divided the sperm of the subjects into three groups (control, 300 µmol/l H 2 O 2 , and 300 µmol/l H 2 O 2 + 1.0 ng/ml GTE) and measured the DFI for each group. They found that GTEtreated sperm exhibited a reduced DNA damage percentage as compared to the 300 µmol/l H 2 O 2 group (21.1% vs 25.2%, P < 0.05) [33]. Similarly, the protection of sperm DNA by GTE has also been demonstrated in rats, bucks, buffalo bulls, and goats [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Giving green tea leaf extract could improve the quality and quantity of spermatozoa (Roychoudhury et al, 2017). Adding green tea extract to the extender could neutralize ROS and prevent DNA damage caused by ROS (Alqawasmeh et al, 2021). Until now, there has been no publication regarding the addition of green tea (Camellia sinensis) leaf extract (GTLE) in skim milk-goose egg yolk (SM-GEY) on the quality of Sapudi ram spermatozoa in 5°C storage.…”
Section: Introductionmentioning
confidence: 99%